Pregnancy outcomes and genetic analysis for fetal ventriculomegaly - Tao, Huimin; Zhang, Lin; Tan, Fangfang; Han, Yu; Wang, Xuezhen; Wu, Jiebin; Zhai, Jingfang (Frontiers in Genetics, 2023)
Fetal ventriculomegaly (VM) is associated with neurodevelopmental disorders, partly caused by genetic factor. To systematically investigate the genetic etiology of fetal VM and related pregnancy outcomes in different subgroups: IVM (isolated VM) and NIVM (non-isolated VM); unilateral and bilateral VM; mild, moderate, and severe VM, a retrospective study including 131 fetuses with VM was carried out from April 2017 to August 2022. 82 cases underwent amniocentesis or cordocentesis, of whom 8 cases (9.8%) were found chromosomal abnormalities by karyotyping. Meanwhile, additional 8 cases (15.7%) with copy number variations (CNVs) were detected by copy number variation sequencing (CNV-seq). The detection rate (DR) of chromosomal abnormalities was higher in NIVM, bilateral VM and severe VM groups. And CNVs frequently occurred in NIVM, bilateral VM and moderate VM groups. In the NIVM group, the incidence of chromosomal aberrations and CNVs in multiple system anomalies (19.0%, 35.7%) was higher than that in single system anomalies (10.0%, 21.1%). After dynamic ultrasound follow-up, 124 cases were available in our cohort. 12 cases were further found other structural abnormalities, and lateral ventricular width was found increased in 8 cases and decreased in 15 cases. Meanwhile, 82 cases underwent fetal brain MRI, 10 cases of brain lesions and 11 cases of progression were additionally identified. With the involvement of a multidisciplinary team, 45 cases opted for termination of pregnancy (TOP) and 79 cases were delivered with live births. 1 infant death and 1 with developmental retardation were finally found during postnatal follow-ups. Hence, CNV-seq combined with karyotyping could effectively improve the diagnostic rate in fetuses with VM. Meanwhile, dynamic ultrasound screening and multidisciplinary evaluation are also essential for assessing the possible outcomes of fetuses with VM.